Peran Advokat dalam Memberikan Jasa Hukum Litigasi dan Nonlitigasi bagi Perusahaan yang Melakukan Pemutusan Hubungan Kerja - Hendri Antonius; Alvi Syahrin; Sunarmi Sunarmi; Mahmul Siregar (CV Rewang Rencang, 2025)
Advocates as law enforcers and providers of legal services in resolving layoff disputes have professional responsibilities in the litigation and non-litigation dimensions in accordance with the Law on Advocates. In litigation, advocates must provide competent legal advice, devise effective strategies, represent clients with integrity, and manage legal risks. In non-litigation, advocates act as neutral mediators, helping to reach a peaceful agreement in accordance with the Employment Law. Advocates must also maintain the confidentiality of client information, be fair, and comply with professional ethics. This dual role involves seeking truth honestly and objectively, protecting clients' legal interests, and complying with ethical and legal standards, in order to realize the goals of the advocate profession in law enforcement.